International financial reporting standards : [as issued at 1 January 2012]. &#x000A - International Accounting Standards Board; International Accounting Standards Board; IFRS Foundation (London : IFRS Foundation., 2012)
The set of volumes sets out the objectives and due process of the International Accounting Standard Board (IASB) and explains the scope, authority and timing of application of IFRSs (including Interpretations).
[V.] 1. Part A. The conceptual framework and requirements
[V.] 2. Part B. The accompanying documents.
Includes index.
oif 17/06/14
Loan
Keywords: Financial statements -- Standards; Accounting -- Standards. &#x000A